Finte element modeling of the behavior of polymethyl-methacrylate (PMMA) during high pressure torsion process. - Ahmed Drai; Benaoumeur Aour; Naima Belayachi; Abderrahim Talha; Noureddine Benseddiq (Fracture and Structural Integrity)
High Pressure Torsion (HPT) is a highly effective super-plastic deformation process for obtaining nano-materials with high performance mechanical properties. In view of its optimization, it is of paramount importance to evaluate the relations between the behavior of the material under the effects of different processing parameters. In this context, this work aims to highlight the plastic strain distribution in the deformed material as a function of the hydrostatic pressure, the torsion angle and the temperature of the material applied during the process. A typical amorphous polymer (Polymethyl-Methacrylate: PMMA) has been tested. Firstly, in order to identify the material parameters of a phenomenological elasto-viscoplastic model compression tests at different temperatures and strain rates have been carried out. Then, the distributions of the effective plastic strain, the equivalent plastic strain rate and the hydrostatic stress were analyzed using finite elements method. Recommendations on process conditions were proclaimed at the end of this work according to the obtained numerical results.